Strong Electrochemiluminescence from MOF Accelerator Enriched Quantum Dots for Enhanced Sensing of Trace cTnI - Yang, Xia; Yu, Yan-Qing; Peng, Ling-Zhi; Lei, Yan-Mei; Chai, Ya-Qin; Yuan, Ruo; Zhuo, Ying (Analytical chemistry (Washington), 2018)
The development of a sensitive and practical electrochemiluminescence (ECL) bioassay relies on the use of ECL signal tags whose signal intensity is high and stable. In this work, strong ECL emission was achieved from metal organic framework (MOF) accelerator enriched quantum dots (CdTe), which were applied as an efficient ECL signal tag for trace biomarker detection. It is particularly noteworthy that a novel mechanism to drastically enhance the ECL intensity of CdTe is established because isoreticular metal organic framework-3 (IRMOF-3) with 2-amino terephthalic acid (2-NH2-BDC) as the organic ligand not only allows for loading a large amount of CdTe via the encapsulating effect and internal/external decoration but also functions as a novel coreactant accelerator for promoting the conversion of coreactant S2O8 2– into the sulfate radical anion (SO4 •–), further boosting the ECL emission of CdTe. On the basis of the simple sandwich immunoreaction approach, cardiac troponin-I antigen (cTnI), a kind of biomarker related with myocardial infarction, was chosen as a detection model using an IRMOF-3-enriched CdTe labeled antibody as the signal probe. This immunosensor demonstrated desirable assay performance for cTnI with a wide response range from 1.1 fg mL–1 to 11 ng mL–1 and a very low detection limit (0.46 fg mL–1). This suggested that the IRMOF-3-enriched CdTe nanocomposite strategy can integrate the coreactant accelerator and luminophore to significantly enhance the ECL intensity and stability, providing a direction for promising ECL tag preparation with broad applications.